Cultural Discontinuities and Intercultural Education: How to Bridge the Value Gap between School and Home - Spajić-Vrkaš, Vedrana (2005)
The concept of cultural discontinuity emerged in the American cultural anthropology in the beginning of the 20th century to describe unexpected disturbance in the individual life cycle that occur as a consequence of raising societal pressures in the period of adolescence. In the beginning of 1960s the term was used by some educational anthropologists in their critique of sociological and psychological explanation of school failure of pupils who belonged to certain minority groups. The deprivation theory, popularized by sociologists, especially those belonging to a functionalist school, was attacked for its fixation on a list of items characterizing white/western middle-income family while the reduced-mental-ability theory, used by psychologists, was criticized for its reliance on culturally insensitive, biased and ethnocentric IQ tests. Both approaches, as educational anthropologists argued, offered rational ground for the promotion of blame-the-victim-strategy. Sociologists contributed to it by seeing cultural differences as social anomalies and psychologists by locating a what in reality was a societal problem into the ‘head’ of an individual. In contrast to them, educational anthropologies offered the cultural discontinuity theory that explains school failure of certain groups of pupils, especially the minorities, in terms of difference in the transmission of values between family and school. Some recent cultural-ecological studies have demonstrated that cultural differences between dominant and minority groups per se do not explain the problem, since not all minority groups face school failure permanently. Problems emerge if education does not lead to adequate societal rewards or if it, directly or indirectly, devalues home cultures. In both cases education may become an instrument for creating, recreating and/or strengthening cultural boundaries to the point where school failure is intentionally produced by minority pupils themselves as a means of cultural survival. Such an oppositional cultural frame of reference becomes a self-perpetuating device for protecting minority group identity. Intercultural education may contribute to solving this problem only if it assists the pupils to see the boundaries, understand their roots and prepare them for action at the community level. Unfortunately, even a brief overview of intercultural programmes demonstrates that they are predominantly content-centred or pupil-centred. The former aims at promoting understanding of cultural differences while the objective of the latter is to prepare culturally or linguistically different students for transition into the regular class. In contrast to them, the community-centred intercultural programmes aim at altering the existing curricula and school organisation by promoting critical understanding and by creating the ground for the exchange of pupils’ knowledge and values. In the presentation the author shall argue that the exchange of different knowledge and values based on three ‘Rs’: Recognition, Respect and Representation is crucial for reducing cultural discontinuities in intercultural education. To justify this perspective, the author will, firstly, explain the relationship among three key terms, i.e. ‘cultural difference’, ‘cultural pluralism’ and ‘interculturalism’ and, secondly, describe the process through which cultural differences have found their place in school curricula. For the purpose of the latter, two phases will be singled out. In the pre-recognition phase, three ‘eras’ will be traced, namely the Golden Ages of Ignorance, the Disturbing Ages of Rhetoric and the Promising Ages of Accommodation. In the recognition phase, three perspectives (monocultural, multicultural and intercultural) will be identified and explained how these perspectives have influenced educational policies and practices. In the end, the author will describe the examples of how the principle of three ‘Rs’ may be integrated into intercultural programmes that, in the one hand, seek to reduce cultural discontinuities between school and home and, in the other hand, aims at promoting cultural pluralism in education.
ENG